Intellectual Property Dispute Resolution Practices: Overlapping Copyright and Industrial Design Rights in Indonesia - Rubben Denova Rohmana; Ahmad M. Ramli; Tasya Safiranita Ramli (Law Development Journal, 2025)
One of the important approaches to be studied on the issue of overlapping copyright and industrial design rights in Indonesia today is the practice of dispute resolution in the judiciary and its impact on stakeholders. In this research, the method used is a statutory approach with analytical descriptive specifications. This research found that Indonesia does not yet have preventive legal arrangements and protection for disputes over copyright and industrial design rights. The results of this study indicate that the settlement of overlapping disputes between copyright and industrial design rights in Indonesia does not reflect the principle of fairness because there is no comprehensive rule of law that can bridge between the two legal regimes. Therefore, a form of harmonization and renewal of copyright law and industrial design rights is needed, to ensure justice and legal certainty for all parties to the practice of dispute resolution.